2016
DOI: 10.1186/s12974-016-0625-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting inflammation as a treatment modality for neuropathic pain in spinal cord injury: a randomized clinical trial

Abstract: BackgroundThe purpose of the present study was to examine the effectiveness of an anti-inflammatory intervention as a treatment for neuropathic pain following spinal cord injury (SCI).MethodsThis randomized, parallel-group, controlled clinical trial (NCT02099890) examined 20 participants with varying levels and severities of SCI, randomized (3:2) to either a 12-week anti-inflammatory diet, or control group. Outcome measures consisted of self-determined indices of pain as assessed using the neuropathic pain que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 62 publications
0
62
0
Order By: Relevance
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the removal of duplicates, a total of 7080 studies was identified in the search. Following full‐text screening, 71 studies were identified for inclusion, with 23 eligible for meta‐analysis. The abstracts for the majority of the papers were not sufficiently detailed to determine whether the full text should be retrieved.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 30% ( n = 21) of the studies were conducted in the USA , with five undertaken in Australia , four conducted in each of Germany , Japan and Spain , and three conducted in each of Denmark , Finland , Sweden , Iran and the Netherlands . Of the included studies, 47 were randomised controlled trials (RCT) , eight were nonrandomised trials , nine were pre–post studies , six were randomised cross‐over trials and one a longitudinal study .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of pro-inflammatory cytokines, including TNF-α, IL-1β, IL-6, and IL-17, have been found to be elevated in animal models of neuropathic pain. The same cytokines have also been found to be increased in the cerebrospinal fluid (CSF) and blood of patients with chronic neuropathic pain conditions [1316]. Therefore, pharmacologically lowering the levels of inflammatory cytokines may reduce pain, which has been demonstrated for various cytokines in both animal models and clinical studies (Table 1).…”
Section: Targeting Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…To this end, our lab performed a randomized controlled trial to explore the efficacy of utilizing an anti-inflammatory diet for the purpose of treating symptoms of neuropathic pain and depression. We found that the implementation of a 3-month anti-inflammatory diet was effective at reducing serum concentrations of proinflammatory mediators, and this reduction translated into significant improvements in both neuropathic pain [10] and depression [11]. Further, participants demonstrated excellent adherence to the diet with an average compliance score of 89%.…”
Section: Introductionmentioning
confidence: 85%